Leveraging Bay' al-Salam Contracts for Agricultural Development in Indonesia: Challenges and Future Strategies - Abrista Devi; Irman Firmansyah; Aam Slamet Rusydiana (Department of Islamic Economics, IPB University, 2026)
This study aims to investigate the challenge that Islamic Financial Institutions (IFIs) encounter while attempting to channel bay' al-salam contract financing for agricultural sector. Afterwards, the appropriate strategy will also be sought for. Using literature such as books, journals, and scientific papers, this research conducts its investigation using a qualitative methodology that incorporates content analysis techniques and in-depth interview to 12 (twelve) experts. This study's findings indicate several obstacles in providing bay' al-salam for the agricultural financing. The internal challenge factors are the absence of assistance from Islamic Financial Institutions, the lack of desire from human resources, and the challenges that originate from the salam finance model technique. A lack of literacy, a lack of supportive regulation, and several alternative financing options are among the external factors. The following are some of the strategies that should be implemented to maximize the effectiveness of the bay' al-salam contract for agricultural financing: enhancing sharia governance and compliance (including strengthening capital), strengthening agricultural infrastructure, leveraging technology, capacity building, and financial literacy, and developing innovative financial solutions (blended finance and flexible payment terms).